Intake of macromolecular nutrition status in pulmonary tuberculosis subjects at the Seputih Raman Health Center, Central Lampung - I Putu Priamaji Girinaja; Rahayu Yekti; Pratiwi Dyah Kusumo (Health Science Journal of Indonesia, 2022)
Background: The condition of pulmonary tuberculosis patients is affected by low nutritional status and this will slow recovery time. The problem of this research is the need to describe the calorie intake of pulmonary tuberculosis patients after receiving education on nutritional patterns high in protein and fat in pulmonary tuberculosis patients at the start of their treatment. In the initial conditions, TB patients generally experience protein and energy deficits, then during the course of treatment for approximately six months, it is necessary to evaluate the nutritional intake profile of TB patients. Therefore the expected goal of this research is to obtain profile data on the intake of energy, protein, fat, and carbohydrates as well as micronutrients. Methods: Research using a descriptive interview approach using a 24-hour food recall questionnaire and www.nutrisurvey.com analysis in the work area of the Seputih Raman Public Health Center, Central Lampung in 2021. Results: Based on nutrisurvey data, subjects were found to be underweight (60%), with the highest carbohydrate intake deficit (80%) compared to intake of protein (46.67%) and fat (53.33%). Conclusion: This shows through our result, the need to emphasize the balance of nutritional intake in the nutrition education of Pulmonary Tuberculosis subjects not only protein and fat intake. Thus tuberculosis patients also need to pay attention to a balanced intake of carbohydrates Keywords: Pulmonary tuberculosis, nutrition intake. Seputih Raman Abstrak Latar Belakang : Kondisi pasien tuberkulosis paru dipengaruhi status gizi yang rendah dan hal ini akan memperlambat waktu pemulihan. Permasalahan penelitian ini perlunya gambaran asupan kalori penderita tuberkulosis paru setelah mendapat edukasi pola gizi tinggi protein dan lemak pada pasien tuberkolusis paru pada awal pengobatan mereka. Dalam kondisi awal, pada umumnya pasien Tuberkulosis mengalami defisit protein dan energi kemudian dalam perjalanan pengobatan selama kurang lebih enam bulan, perlu dilakukan evaluasi melihat profil asupan nutrisi pasien Tuberkulosis. Oleh karenanya tujuan yang diharapkan dalam penelitian ini adalah didapatkan profil data asupan energi, protein, lemak dan karbohidrat juga mikronutrien. Metode: Penelitian pendekatan deskriptif wawancara dengan alat ukur kuesioner food recall 24 jam dan analisa www.nutrisurvey.com di daerah kerja puskesmas Seputih Raman, Lampung Tengah Tahun 2021. Hasil: Berdasarkan data analisa nutrisurvey, didapatkan 60% pasien status gizi kurus, dengan angka defisit asupan karbohidrat paling tinggi (80%) dibandingkan asupan protein (46,67%) dan lemak (53,33%). Kesimpulan: Melalui hasil penelitian kami, hal ini menunjukkan perlunya menekankan keseimbangan asupan gizi pada edukasi gizi pasien Tuberkulosis Paru bukan hanya pada asupan protein dan lemak, dengan demikian pasien Tuberkulosis juga perlu memperhatikan asupan karbohidrat yang seimbang. Kata kunci: Tuberkulosis paru, asupan nutrisi, Seputih Raman.